PERANCANGAN APLIKASI PENJUALAN MOBIL BEKAS DI CV. SHANDY MOTOR BERBASIS WEB - Minarni, S.Si., M.T; Beri Antoni (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2013)
A very tight competition is currently trading world requires a good promotional strategy. Promotional strategies to attract and reach more consumers and also to meet the needs of consumers. CV. Shandy Motor is a car showroom that specializes in buying and selling used cars, promotions are still using paper facility, brochures, and other similar facilities. Barriers - the barriers that make it less effective promotional product. Therefore, the authors researched to design an "application design information systems web-based used car sales" to simplify the used car market products in perjual traded in CV. Shandy Motor. And facilitate people who want to sell his car. Application used to create applications used car sales information system is a web-based XAMPP, MySQL. The results of this final task is in the form of an information system used car sales web-based web information can be used for buying and selling used cars as a means of promotion, which will be taken into consideration for prospective buyers.